[PP.37.02] ASSOCIATION BETWEEN TWO ANGIOGRAPHIC SUBTYPES OF RENAL ARTERY FIBROMUSCULAR DYSPLASIA AND CLINICAL CHARACTERITSIC: THE PRELIMINARY DATA OF THE REGISTRY FOR FIBROMUSCULAR DYSPLASIA. (September 2016) - Florczak, E.; Miadziolko, M.; Warchol-Celinska, E.; Januszewicz, M.; Michalowska, I.; Hanus, K.; Jozwik-Plebanek, K.; Prejbisz, A.; Talarowska, P.; Kadziela, J.; Nazarewski, S.; Madej, K.; et al.
Abstract : Objective: To compare clinical presentation of two angiographic subtypes of renal fibromuscular dysplasia (FMD) in patients with renal FMD enrolled to ARCADIA-POL registry. Design and method: From 84 patients with confirmed FMD in any vascular bed enrolled in the ARCADIA-POL registry in 2015 (instituted on the basis of as Polish-French collaboration), we analyzed 74 patients (54F, 20 M, mean age:41.7 ± 15.2 years, range:18–72) with renal FMD. All patients underwent evaluation including ambulatory blood pressure monitoring, biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. In this analysis we divided patients into two groups according to angiographic subtypes of renal FMD lesions (Savard et al. Circulation 2012). FMD lesions were classified according to angio-CT as multifocal if there were at least 2 stenoses in the same arterial segment (Group 1); otherwise as unifocal (Group2). Results: Of 74 patients with renal FMD, 48 pts (64.9%) were classified as multifocal (Group 1) and 26 pts (35.1%) as unifocal (Group 2). Patients in Group 1 as compared to Group 2 were characterized by non-significantly higher rate of females (79.2vs.61.5%; p = 0.103). At evaluation there were no differences in age, frequency of smokers, hypertension rate, median number of antihypertensive medications, nor in office and 24-hour blood pressure values. Group 1 differed significantly from Group 2 in mean age at diagnosis of FMD (29.2 ± 14.2vs.41.0 ± 15.5 years, p = 0.003) and hypertension (23.4 ± 12.6vs.34.8 ± 14.0 years, p = 0.002). Among 27 patients in whom FMD was diagnosed at age over 40 years only 4 (14.8%) had unifocal and 20 (85.2%) had multifocal type. Group 1 were characterized by non-significantly higher proportion of patients with more than one vascular bed involved (36% vs. 54.2 %, p = 0.14). Aneurysm of renal artery was found in 10 pts with multifocal and in 3 patients with unifocal lesions (20.8% vs.11.5 %, p = 0.316). In two patients with multifocal and none of patients with unifocal FMD renal artery dissection was observed. Conclusions: A binary angiographic classification in unifocal and multifocal FMD discriminated two groups of patients with different age at diagnosis of FMD and hypertension, as well as tendency towards different proportion of multiple beds involvement and vascular complications.